2019
DOI: 10.2528/pierl19052905
|View full text |Cite
|
Sign up to set email alerts
|

Shared Aperture Microstrip Patch Antenna Array for L and S-Bands

Abstract: A dual mode shared aperture antenna consisting of two planer arrays of ring antennas is designed for L and S bands. The array of larger dimension surrounds the array of smaller dimension. The antennas are isolated from one another and fed separately. The antenna dimensions are optimized and prototyped. The antennas radiate separately in L and S bands with least coupling or no coupling. Measured results are in agreement with the simulations, depicting good performance in terms of impedance bandwidth, isolation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A single-layer antenna array is an element array in X and Ku bands. Compared to the SAAs in [5][6][7][8][9][10][11], [13], and [16][17][18][19][20][21][22], the suggested SAA has an FR of 1.426, better gains, and better band isolation. The dual-band prototype has a compact, multi-layer, planar SAA architect.…”
Section: B Ku-band 5-element Designmentioning
confidence: 99%
See 1 more Smart Citation
“…A single-layer antenna array is an element array in X and Ku bands. Compared to the SAAs in [5][6][7][8][9][10][11], [13], and [16][17][18][19][20][21][22], the suggested SAA has an FR of 1.426, better gains, and better band isolation. The dual-band prototype has a compact, multi-layer, planar SAA architect.…”
Section: B Ku-band 5-element Designmentioning
confidence: 99%
“…The combination of patches and feed layers results in an exceedingly small antenna that is excellent for low-weight applications such as spaceborne SAR [16]. In [17], L and S bands, a dual-mode shared apert antenna consisting of two planer arrays of ring antennas is designed. The antennas are isolated and fed separately from one another.…”
Section: Introduction Sar Technology Bymentioning
confidence: 99%
“…Another technique is to design a dual-band array comprising interleaved printed folded dipoles, which are resonant at octave-separated frequency bands (1 and 2 GHz), with individual feeds for each element [3]. Shared aperture concept has been used to design dual band antenna arrays in L and S bands [4]. However, the reported shared aperture antenna designs [5][6][7][8] are mostly complicated and bulky which makes their fabrication expensive and challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Angular ring patch antenna was first reported in year 1985, by IJ Bahal for biomedical application. Thereafter, only few research have been reported on these antennas such as, theory and experiment on the annular-ring microstrip antenna, shared aperture microstrip patch antenna array for L and S-Bands, analysis of a gap-coupled stacked annular-ring microstrip antenna, compact stacked circularly polarized annular-ring microstrip antenna for GPS applications, annular-ring microstrip patch antenna with finite ground plane for ultra-wideband applications, compact concentric annular-ring patch antenna for triple-frequency operation, comparison of several novel annular-ring microstrip patch antennas for circular polarization, analysis of two-concentric annular-ring microstrip antenna, and broadband circularly polarized annular-ring microstrip antenna [1][2][3][4][5][6][7][8][9][10]. All above reported papers has some limitations such as complicated geometry, lacks theoretical analysis for defected ground with microstrip line feed, circuit diagram at Radio frequency were not proposed for designed antenna and theoretical, simulated and experimental results were not compared.…”
Section: Introductionmentioning
confidence: 99%